ADVANCEMENTS IN AI FOR MULTIMEDIA COMMUNICATION NETWORKS: REVOLUTIONIZING CONNECTIVITY AND CONTENT DELIVERY (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the transformative role of Artificial Intelligence (AI) in multimedia communication networks. It investigates how AI-driven solutions are revolutionizing various aspects of communication, including network optimization, personalized content delivery, security, and privacy. Through a comprehensive examination of AI applications in telecommunications systems, the article highlights the potential of AI to enhance network efficiency, improve user experiences, and ensure the security and privacy of communication channels. Additionally, it discusses emerging trends, ethical considerations, and technological challenges in the integration of AI into multimedia communication networks, offering insights into the future direction of this dynamic field.